Economic Empowerment in Mendawai Social Complex: Pathways to Independence for Poor Urban Communities in Palangka Raya - Indra Nugraha; Ratna Sari; Teguh Santoso (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Urban poverty remains a persistent challenge in many Indonesian cities, including Palangka Raya, where the Mendawai Social Complex houses vulnerable communities striving for economic independence. This study explores pathways to economic empowerment for poor urban residents by assessing community driven initiatives, institutional support structures, and livelihood strategies that foster sustainable self reliance. Employing a mixed methods approach, the research integrates quantitative surveys of household income changes with qualitative interviews involving community members, local leaders, and development stakeholders. Findings reveal that participation in skills training programs, access to microfinance, and community led savings groups positively correlate with increased income generation and economic resilience. Moreover, results indicate that strengthening social networks and local leadership enhances market access for small enterprises and encourages collective problem solving. However, persistent barriers — including limited capital, formal employment opportunities, and gaps in policy coordination — continue to impede full economic autonomy. The study underscores the importance of integrated strategies that combine economic interventions with social capital development. Policy recommendations emphasize scaling community cooperatives, expanding vocational training, and fostering collaborations between government, NGOs, and private sector partners. These pathways not only improve livelihoods but also contribute to inclusive urban development and long term socioeconomic stability for marginalized populations in Palangka Raya.